PENERAPAN VARIASI MENGAJAR, KETERAMPILAN MENJELASKAN, SERTA MEMBUKA DAN MENUTUP PEMBELAJARAN SEBAGAI STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN ABAD 21 DI SEKOLAH DASAR - Rabbiah Al Adawiyah; Ranggita Dwi Syahla; Silfa Ayu Prastika; Vera Arefanda; Zulfadewina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of 21st century education requires teachers to master various innovative learning strategies to improve the quality of the teaching and learning process, especially at the elementary school level. This article aims to examine the application of teaching variations, explanation skills, and strategies for opening and closing learning as an effort to improve the quality of learning. Teaching variations are applied to create an interesting learning atmosphere and accommodate various student learning styles, while explanation skills function to clarify concepts through systematic, concrete, and contextual delivery. On the other hand, the strategy for opening learning plays a role in arousing student motivation, while closing learning helps students reflect and strengthen their understanding of the material. This study shows that the application of these three aspects consistently can increase active participation, conceptual understanding, and critical thinking skills of students. Therefore, strengthening teacher competence in applying teaching variations, explanation skills, and opening and closing learning effectively is very important to support the achievement of 21st century education goals in elementary schools.